Impact of Expenditure on the Financial Condition of the City Bus Transport in Sofia - Milusheva, Nadezhda (Research Papers, 2022)
The main costs in transport companies can be spent on the purchase and maintenance of moving parts, fuels, taxes and fees, insurance, the introduction of drivers and investment in new technologies. The size of the calculations includes showing the impact of cash flows, profitability, financial independence and effective financial result.The main problem that is monitored is the lack of efficient allocation of resources when transporting passengers by city buses, which leads to inefficiency of the public service provided to citizens.The aim of the study in the same study is to establish the impact of the distribution of fixed and variable costs on the financial sustainability of urban bus transport, on which to provide guidelines to support the financial situation.The research thesis is that it will improve your decisions related to the distribution of costs, will lead to increased financial results and will achieve the financial sustainability of urban bus transport.A more productive transport product can be produced through variability and redistribution of resources; controlling and reducing the technological mileage; updating the schedules according to the specific situation; reducing fuel consumption by replacing it with environmentally friendly, as well as shared use of operational reserve drivers, which will allow optimizing the work process and achieving financial sustainability of urban bus transport in the capital.
Keywords: Improvement; Costs; Financial condition; Urban bus transport; Optimization